Comment on Jones et al. Application of a Novel Algorithm for Expanding Newborn Screening for Inherited Metabolic Disorders across Europe. Int. J. Neonatal Screen. 2022, 8, 20 - Rose Maase; Marleen E. Jansen; Marie-Louise Heijnen; Eugenie Dekkers (MDPI AG, 2023)
With innovations in both the screening methodologies and treatment of diseases, newborn screening (NBS) programmes are confronted with an increasing number of candidate diseases [...]